Benzyl viologen-assisted simultaneous exfoliation and n-doping of MoS2 nanosheets via a solution process. Issue 22 (24th May 2017) - Jo, Kiyoung; Choi, Jaeyoo; Kim, Heesuk
Abstract : Simultaneous exfoliation and n-doping of a TMD, i.e., MoS2, is achieved via a solution process using benzyl viologen (BV) and hydrazine. Abstract : Modulating the electrical properties of transition metal dichalcogenides (TMDs) is of fundamental importance for applications in nanoelectronic devices and can be achieved through the exfoliation of a bulk material into nanosheets or controlled doping. In this study, the simultaneous exfoliation and n-doping of a TMD, i.e., MoS2, is achieved for the first time via a solution process using benzyl viologen (BV) and hydrazine. The MoS2 sample exfoliated by the BV molecules has an average thickness of 2.68 nm and a lateral size of 200–900 nm, indicating bi- or tri-layered MoS2 nanosheets. These nanosheets have an electrical conductivity (2.28 × 10 −1 S m −1 ) that is higher by one order of magnitude than that of bulk MoS2 due to the effective n-doping by BV molecules. As a proof of concept, the thermoelectric properties of the exfoliated MoS2 –BV nanosheets are characterized, which reveals an enhanced Seebeck coefficient (−360 μV K −1 ) due to quantum confinement by successful exfoliation. The electrical conductivity and Seebeck coefficient are the highest values among those of MoS2 nanosheets previously prepared by a solution-process. This newly proposed strategy for simultaneous exfoliation and doping can be used to control the electrical properties of MoS2, thus showing great potential for further development of 2D TMD-based electronic and energy devices.